Weibel Palade Bodies: Unique Secretory Organelles of Endothelial Cells that Control Blood Vessel Homeostasis - Naß, Johannes; Terglane, Julian; Gerke, Volker (Frontiers in Cell and Developmental Biology, 2021)
Vascular endothelial cells produce and release compounds regulating vascular tone, blood vessel growth and differentiation, plasma composition, coagulation and fibrinolysis, and also engage in interactions with blood cells thereby controlling hemostasis and acute inflammatory reactions. These interactions have to be tightly regulated to guarantee smooth blood flow in normal physiology, but also allow specific and often local responses to blood vessel injury and infectious or inflammatory insults. To cope with these challenges, endothelial cells have the remarkable capability of rapidly changing their surface properties from non-adhesive (supporting unrestricted blood flow) to adhesive (capturing circulating blood cells). This is brought about by the evoked secretion of major adhesion receptors for platelets (von-Willebrand factor, VWF) and leukocytes (P-selectin) which are stored in a ready-to-be-used form in specialized secretory granules, the Weibel-Palade bodies (WPB). WPB are unique, lysosome related organelles that form at the trans-Golgi network and further mature by receiving material from the endolysosomal system. Failure to produce correctly matured VWF and release it through regulated WPB exocytosis results in pathologies, most importantly von-Willebrand disease, the most common inherited blood clotting disorder. The biogenesis of WPB, their intracellular motility and their fusion with the plasma membrane are regulated by a complex interplay of proteins and lipids, involving Rab proteins and their effectors, cytoskeletal components as well as membrane tethering and fusion machineries. This review will discuss aspects of WPB biogenesis, trafficking and exocytosis focussing on recent findings describing factors contributing to WPB maturation, WPB-actin interactions and WPB-plasma membrane tethering and fusion.